Sustainability Reporting (ESG) Quality: a Comparative Study Between Manufacturing and Banking Companies - Juanda, Ahmad; Setyawan, Setu; Naseer, Maryam Shahuneeza (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to examine the influence of standalone CSR reports, GRI standards, and external assurance services on the quality of ESG sustainability reports between 2 sectors, namely the manufacturing and banking sectors. The data used in this study were 47 banking sectors and 163 manufacturing sectors. The results of this study are expected to provide an understanding of cross-sector sustainability and assist stakeholders regarding information on sustainable reporting practices. This study contributes, firstly, by providing evidence on the level of quality of sustainability reporting in two different sectors, namely the banking and manufacturing sectors. Secondly, this study focuses on standalone CSR disclosures, the use of GRI standards, and external assurance services. The findings show that the quality of ESG sustainability reports in the banking sector is more influenced by external assurance services. Banking companies assume that external assurance services can improve the credibility and quality of sustainability report information if the assurance process is carried out with a focus on meeting stakeholder needs and based on applicable assurance principles and standards. Meanwhile, in the manufacturing sector, the quality of ESG sustainability reports in banking companies is more influenced by their own CSR reports. CSR presented by a separate company is an important type of report because it shows the company's commitment to addressing environmental issues.